Mental health case management a practical guide - Eack, Shaun M.; Anderson, Carol M. 1939-; Greeno, Catherine G. (SAGE Publications, 2017)
This book is a practical guide for students and practitioners to understand the nuts and bolts of case management. It is not intended to be a theoretical overview of case management, rather, a brief supplemental text that walks the student and new practitioner through the essential responsibilities and functions of a case manager. While many students end up working in mental health agencies as case managers, they most often do not receive any preparation for the kind of work they will be doing. This book addresses that need by outlining the essential areas of focus of a case manager